2017
DOI: 10.1016/j.molcel.2017.08.007
|View full text |Cite|
|
Sign up to set email alerts
|

The ATPase Fap7 Tests the Ability to Carry Out Translocation-like Conformational Changes and Releases Dim1 during 40S Ribosome Maturation

Abstract: SUMMARY Late in their maturation, nascent small (40S) ribosomal subunits bind 60S subunits to produce 80S-like ribosomes. Due to the analogy of this translation-like cycle to actual translation, and because 80S-like ribosomes do not produce any protein, it was suggested that this represents a quality-control mechanism for subunit functionality. Here, we use genetic and biochemical experiments to show that the essential ATPase Fap7 promotes formation of the rotated state, a key intermediate in translocation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 62 publications
7
81
0
Order By: Relevance
“…Nob1 blocks mRNA recruitment to 20S pre-rRNA-containing ribosomes Nascent 40S subunits arrive in the cytoplasm bound to seven assembly factors, which block premature translation initiation on immature assembly intermediates by preventing the association of translation initiation factors (Strunk et al, 2012). These assembly factors are then released in a series of regulated steps that form part of a translation-like cycle, which couples the release of these factors to quality control steps (Collins et al, 2018;Ghalei et al, 2017;Strunk et al, 2012). Furthermore, when pre-mature ribosomes do escape into the translating pool, they are unable to support cell viability (Soudet et al, 2010;Strunk et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nob1 blocks mRNA recruitment to 20S pre-rRNA-containing ribosomes Nascent 40S subunits arrive in the cytoplasm bound to seven assembly factors, which block premature translation initiation on immature assembly intermediates by preventing the association of translation initiation factors (Strunk et al, 2012). These assembly factors are then released in a series of regulated steps that form part of a translation-like cycle, which couples the release of these factors to quality control steps (Collins et al, 2018;Ghalei et al, 2017;Strunk et al, 2012). Furthermore, when pre-mature ribosomes do escape into the translating pool, they are unable to support cell viability (Soudet et al, 2010;Strunk et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent misassembled ribosomes from reaching the translating pool, the premature small (pre-40S) ribosomal subunit undergoes a series of quality control checkpoints during late cytoplasmic maturation that verify proper ribosomal structure and function (Collins et al, 2018;Ghalei et al, 2017;Strunk et al, 2012). The importance of these checkpoints for cellular function is illustrated by the numerous diseases caused by haploinsufficiency or mutations in ribosomal proteins and assembly factors.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to YBEY, Fap7 forms a stoichiometric complex with uS11/Rps14 (93) and helps to recruit it to the nascent SSU (94), which represents a final checkpoint before the fully assembled SSU is released for translation (95). In fact, all known uS11 homologues have a long disordered positively charged C-terminal extension, which needs to be correctly positioned in the vicinity of the helix-45 of the SSU rRNA ( Figure 6E) (96).…”
Section: Discussionmentioning
confidence: 99%
“…The sedimentation profile showed that the majority of Tsr1-FPZ pre-40S particles presented a peak position very similar to that of mature 40S ribosomal subunits, thus migrating as "free" pre-40S subunits. A smaller peak of heavier fractions indicates that Tsr1-FPZ could be found in bigger complexes, some of them probably being 80S-like particles [29,30,34,35] (Figure 1a, upper panel). Transmission electron microscopy (TEM) observations after negative staining confirmed that the particles sedimenting on lighter fractions had the overall size and shape of 40S subunits, while heavier fractions contained larger, rounder objects, with dimensions compatible with 80S-like particles (Figure 1a, lower panel).…”
Section: Proteomic Characterization Of Tsr1-purified Pre-40s Particlesmentioning
confidence: 99%